2002
DOI: 10.1108/13527600210797497
|View full text |Cite
|
Sign up to set email alerts
|

The tropical fish problem revisited: a Malaysian perspective

Abstract: This article revisits cross‐cultural management in Malaysia by challenging some fundamental assumptions. Most models of culture, such as Hofstede’s, assume that a country is reasonably homogeneous to make an analysis meaningful. We argue, conceptually and by providing empirical data that Malaysia is not a homogeneous country, and therefore Hofstede’s model is not suitable in Malaysia. Although this article deals with Malaysia specifically, there are a number of countries where Hofstede’s assumption might not w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…These results are consistent with previous research in cultural values between Malays and non-Malays (e.g. Fontaine et al, 2002, Abdullah and Low, 2001, Fontaine and Richardson, 2005. Generally, Malay value religion more than non-Malays do.…”
Section: Discussion and Managerial Implicationssupporting
confidence: 92%
“…These results are consistent with previous research in cultural values between Malays and non-Malays (e.g. Fontaine et al, 2002, Abdullah and Low, 2001, Fontaine and Richardson, 2005. Generally, Malay value religion more than non-Malays do.…”
Section: Discussion and Managerial Implicationssupporting
confidence: 92%
“…However, the value preference of Malaysian ethnic groups will inevitably be influenced by the school cultural environment as claimed by Fontaine, Richardson, and Foong (2002) even though cultural influence in terms of school types, gender, and ethnicity has been minimized at the stage of preliminarily analysis statistically. In addressing this limitation, a cross-cultural comparative study of Teacher Commitment is strongly suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Fontaine et al, 2002;Bubeck and Bilsky, 2004;Saroglou et al, 2004) and predict human behaviour and attitudes, such as: social behaviours of various types (e.g. Reallo et al, 2002;Goodwin et al, 2004;Kurman and Ronen-Ellon, 2004;Alkire, 2005); family behaviour (e.g.…”
Section: Values Theory and The Portrait Value Questionnairementioning
confidence: 99%